If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2e + 3) = 40 Reorder the terms: 8(3 + 2e) = 40 (3 * 8 + 2e * 8) = 40 (24 + 16e) = 40 Solving 24 + 16e = 40 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 16e = 40 + -24 Combine like terms: 24 + -24 = 0 0 + 16e = 40 + -24 16e = 40 + -24 Combine like terms: 40 + -24 = 16 16e = 16 Divide each side by '16'. e = 1 Simplifying e = 1
| 2400=(x*.76)+(y*.4) | | 4+3x=7+2x-3 | | X-11x=-28 | | 10x^2+27+5=0 | | (8x-5)+(-2x+7)= | | x=e^5y | | 014x+0.9(x-2)=0.01(4x-2) | | 24*.75x=18x | | Log(6x+4)=2 | | 5(a-10)=45 | | 16=103a | | 24*.75y=18y | | 2x+49x-9x+21x+5x= | | (6x+4)=2 | | (u+4)10=80 | | 3+4=6x+x | | 4y+5=3(2y-7) | | 9(18x-3)= | | (q-9)4=8 | | 2ln(7x+6)+19 = 13 | | 4(z-4)+5z=6z+11 | | X+7x+1=0 | | 2.5z=10 | | 2(4X-7)+12=4X+14 | | x+2/4-2x+1/3=-x/6 | | -3(4x+2)=-8(6x+3) | | 9ab+9b-49b+8ab-12= | | 36x-1=0 | | -16x+12=39-7x | | 3z-1=2z | | 6x+38x+40=0 | | 2(x+4)+3(2x-5)=5 |